Discrimination Features of Chromatic Figures in Various Background Characteristics - Y A Chudina (Peoples' Friendship University of Russia (RUDN University), 2013)
Visual recognition features of images with different figure-ground segregation have been considered in the article. The research was carried out within the framework of Sokolov and Izmaylov's spherical model and was based on the construction of color objects discrimination models depending on the changes of background characteristics. The research has revealed the specific influence of the background on figure discrimination. The derived models reflect the mechanisms of the all-in-one perception of the visual space.